Comments on the morphology and biology of Pammene castanicola Trematerra & Clausi, 2009 (Lepidoptera: Tortricidae: Grapholitini) - Clausi, Mirella; Leone, Diego; Oreste, Monica; Tarasco, Eustachio (Zootaxa, 2016)
Many insects are reported to damage cultivated chestnut (Castanea sativa Mill.; Fagaceae) in Italy, but the most important pests of chestnut fruits are weevils (Curculio elephas Gyll. and Curculio glandium Marsh.; Curculionidae) and tortricid moths (Pammene and Cydia; Tortricidae) (Pollini, 1998, Speranza, 1999). The larvae of the tortricid pests develop internally, tunnelling in the fruits and eating the endocarp (Rotundo et al. 1991), which significantly reduces nut quality and commercial value. The most damaging tortricid moths in the Italian chestnut industry are Pammene fasciana (Linnaeus) (the early chestnut moth), Cydia fagiglandana (Zeller) (the intermediate chestnut moth), and Cydia splendana (Hübner) (the late chestnut moth) (Pedrazzoli et al. 2012). Pammene castanicola Trematerra & Clausi, 2009 was recently described from chestnut woods near Etna Vulcan, Sicily (Trematerra and Clausi 2009), and it is known only from the vicinity of the type locality. It is similar to Pammene fasciana in morphological and biological features, and it was previously misidentified as P. fasciana. We provide observations on the biology and larval development and present detailed descriptions and illustrations of the mature larva of P. castanicola, with comments on the differences between P. castanicola and P. fasciana.